2006
DOI: 10.1213/01.ane.0000217208.51017.56
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Hypertonic Saline for Treating Intracranial Hypertension After Traumatic Brain Injury

Abstract: The past decade has witnessed a resurgence of interest in the use of hypertonic saline for low-volume resuscitation after trauma. Preliminary studies suggested that benefits are limited to a subgroup of trauma patients with brain injury, but a recent study of prehospital administration of hypertonic saline to patients with traumatic brain injury failed to confirm a benefit. Animal and human studies have demonstrated that hypertonic saline has clinically desirable physiological effects on cerebral blood flow, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
1
14

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(76 citation statements)
references
References 78 publications
2
59
1
14
Order By: Relevance
“…The literature from HICs (both adult and pediatric) has shown low rates of complications in a PICU setting [7,9,18,19]. Our study demonstrates that administration of 3% HTS through peripheral IV line is safe.…”
Section: Discussionmentioning
confidence: 52%
“…The literature from HICs (both adult and pediatric) has shown low rates of complications in a PICU setting [7,9,18,19]. Our study demonstrates that administration of 3% HTS through peripheral IV line is safe.…”
Section: Discussionmentioning
confidence: 52%
“…[12] In addition, the osmotic diuresis that accompanies mannitol administration may lead to hypotension, especially in hypovolemic patients, and may worsen secondary brain injury in TBI patients. [95] However, this review found that 60 (92%) identifi ed papers used mannitol to control ICP in pre-hospital settings. Twenty-eight (43%) papers even reported that they administered mannitol to all of their TBI patients (Table 7).…”
Section: Brain Herniationmentioning
confidence: 99%
“…27,[33][34][35] Bolus dosing regimens vary within the literature. Some authors advocate the use of 2 mL/kg of 7.5% 27 for the control of elevated ICP, while others have used 250 mL boluses of 3% 36 or 30 mL of 23.4%. 37 To date, there are no direct comparison studies between these dosing regimens.…”
Section: Traumatic Brain Injurymentioning
confidence: 99%